2013
DOI: 10.1155/2013/172518
|View full text |Cite
|
Sign up to set email alerts
|

Moderating Material to Compensate the Drawback of High Minor Actinide Containing Transmutation Fuel on the Feedback Effects in SFR Cores

Abstract: The use of fine distributed moderating material to enhance the feedback effects and to reduce the sodium void effecting SFRs is described. The drawback on the feedback effects due to the introduction of minor actinides into SFR fuel is analyzed. The possibility of compensation of the effect of the minor actinides on the feedback effects by the use of fine distributed moderating material is demonstrated. The consequences of the introduction of fine distributed moderating material into fuel assemblies with fuel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
2
5
0
Order By: Relevance
“…However, 12 ZrH 1.8 moderator rods are used in all the fuel assemblies to further reduce the sodium void worth and improve the Doppler coefficient by softening the neutron spectrum. On the other hand, ZrH 1.8 has low thermal stability issues but the literature shows that these issues can be solved with the use of yttrium hydride, which is thermally stable up to 1300 • C and has similar neutronic effects to zirconium hydride [10,28]. In addition, the active core height is reduced from 90 cm to 80 cm to reduce sodium void worth.…”
Section: Advanced Uranium-free Fueled Burner Coresmentioning
confidence: 99%
See 1 more Smart Citation
“…However, 12 ZrH 1.8 moderator rods are used in all the fuel assemblies to further reduce the sodium void worth and improve the Doppler coefficient by softening the neutron spectrum. On the other hand, ZrH 1.8 has low thermal stability issues but the literature shows that these issues can be solved with the use of yttrium hydride, which is thermally stable up to 1300 • C and has similar neutronic effects to zirconium hydride [10,28]. In addition, the active core height is reduced from 90 cm to 80 cm to reduce sodium void worth.…”
Section: Advanced Uranium-free Fueled Burner Coresmentioning
confidence: 99%
“…low thermal stability issues but the literature shows that these issues can be solved with the use of yttrium hydride, which is thermally stable up to 1300 °C and has similar neutronic effects to zirconium hydride [10,28]. In addition, the active core height is reduced from 90 cm to 80 cm to reduce sodium void worth.…”
Section: Advanced Uranium-free Fueled Burner Coresmentioning
confidence: 99%
“…For a solid fuel critical fast reactor, increasing the transmutation time requires a considerably high initial excess reactivity of the reactor core, posing a challenge to reactor core safety control 3 . In short, the above drawbacks for ADS and fast reactor inevitably limit the potential of TRUs transmutation in the two kinds of nuclear system 17 …”
Section: Introductionmentioning
confidence: 99%
“…3 In short, the above drawbacks for ADS and fast reactor inevitably limit the potential of TRUs transmutation in the two kinds of nuclear system. 17 TRUs can also be transmuted in a molten salt fast reactor by dissolving them in molten salt without using a moderator in the reactor core. Liquid molten salt serves as both nuclear fuel carrier and coolant in the reactor core.…”
Section: Introductionmentioning
confidence: 99%
“…The study has been focused in the first step on the choice of the ideal moderating material [8,9] and in a second step on the optimization of the placing of the applied zirconium hydride inside the fuel assembly to obtain the optimal effect in power distribution and burnup as well as during transients [10,11]. In the third step the focus has been put on the influence of the moderating material on the transmutation performance of a SFR [12,13]. It is shown that the insertion of fine distributed material has nearly no influence on the transmutation performance itself, but it opens the possibility to increase the minor actinide amount due to the compensation of the effects of minor actinides on the feedback coefficients.…”
Section: Introductionmentioning
confidence: 99%